Temporal Discounting of Money and Face Masks During the COVID-19 Pandemic: The Role of Hoarding Level - Cannito, Loreta; Anzani, Stefano; Bortolotti, Alessandro; Palumbo, Rocco; Ceccato, Irene; Di Crosta, Adolfo; Di Domenico, Alberto; Palumbo, Riccardo (Frontiers in Psychology, 2021)
The current study examines individual hoarding levels on temporal discounting of different commodities during the COVID-19 pandemic. Based on their hoarding level, participants were assigned to the Hoarding Group (HG) or the Non-Hoarding Group (NHG). Participants performed two delay discounting tasks: a traditional task with monetary options and a modified task, where money was replaced with disposable surgical masks, a needed commodity during the pandemic. Results revealed a stronger preference for immediate commodity, therefore a higher discount rate, when evaluating surgical masks compared to money in the whole sample, and an overall higher tendency in discounting both type of rewards in the NHG compared to the HG. Moreover, non-hoarders discounted money significantly more than hoarders, while no significant differences were detected in the surgical mask version of the task. Possible explanations for this result are discussed in the light of a situational frame that makes salient the notion of scarcity, like the one induced by the COVID-19 pandemic. The hoarding dimension of cluttering was found to be the only dimension to significantly correlate with the discount rate on surgical masks. Altogether, these findings shed light on the role of general hoarding level and specific hoarding dimensions on intertemporal preferences with different commodities by contributing to the theoretical debate about impulsivity in hoarders’ behavior. Furthermore, the present results help to understand the general population’s preferences during times of crisis, thus contributing to the investigation of the effects of COVID-19 on consumers’ behavior.